2021
DOI: 10.1152/japplphysiol.00742.2020
|View full text |Cite
|
Sign up to set email alerts
|

Functional pathophysiology of SARS-CoV-2-induced acute lung injury and clinical implications

Abstract: The worldwide pandemic caused by the SARS-CoV-2 virus has resulted in over 84,407,000 cases with over 1,800,000 deaths when this paper was submitted, with comorbidities such as gender, race, age, body mass, diabetes, and hypertension greatly exacerbating mortality. This review will analyze the rapidly increasing knowledge of COVID-19 induced lung pathophysiology. Although controversial, the acute respiratory distress syndrome (ARDS) associated with COVID-19 (CARDS) seems to present as two distinct phenotypes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 145 publications
(248 reference statements)
2
42
0
3
Order By: Relevance
“…Severe covid-19 pneumonia as defined by NIH1 overlaps significantly with the clinical definition of “classic” ARDS 60. However, several unique pathophysiological processes are postulated to be at play for CARDS, such as intravascular thrombosis caused by loss of endothelial barrier, prominent loss of hypoxic pulmonary vasoconstriction resulting from endothelial dysfunction, and excessive blood flow to collapsed lung tissue 61. Further, not all case series provide a clear semantic distinction between severe covid-19 pneumonia and CARDS, which confounds interpretation.…”
Section: Respiratory Care For Severe Covid-19 Pneumoniamentioning
confidence: 99%
“…Severe covid-19 pneumonia as defined by NIH1 overlaps significantly with the clinical definition of “classic” ARDS 60. However, several unique pathophysiological processes are postulated to be at play for CARDS, such as intravascular thrombosis caused by loss of endothelial barrier, prominent loss of hypoxic pulmonary vasoconstriction resulting from endothelial dysfunction, and excessive blood flow to collapsed lung tissue 61. Further, not all case series provide a clear semantic distinction between severe covid-19 pneumonia and CARDS, which confounds interpretation.…”
Section: Respiratory Care For Severe Covid-19 Pneumoniamentioning
confidence: 99%
“…While HPV is recognized as an important mechanism of increased pulmonary tone in non-COVID ARDS [91], its role in COVID-19 ARDS is currently controversial. Indeed, the latter may present as two distinct phenotypes, characterized by low or high elastance [93]. In the former, it has been claimed that inefficient HPV could favor massive intrapulmonary shunts in the affected lung areas, leading to profound hypoxemia with minimal hypoxemiarelated symptoms, as reported in 32% of COVID-19 patients [94].…”
Section: Hypoxic Vasoconstrictionmentioning
confidence: 99%
“…They challenged the concept of the two distinct phenotypes that were proposed in CARDS pathophysiology. Another study showed that CARDS and ARDS respiratory mechanics are remarkably overlapped so the standard ventilation strategy could be applied to these patients [ 119 ]. Naidoo et al , also found the clinical picture manifested in COVID-19 patients was largely consistent with classical ARDS so using traditional LPVS may be acceptable and do not warrant change at this stage.…”
Section: Ventilation Strategiesmentioning
confidence: 99%